Seven bad ideas how mainstream economists have damaged America and the world - Madrick, Jeffrey G. (New York Alfred A. Knopf, 2014)
"The author of the widely praised Age of Greed now gives us a bold indictment of some of our most accepted economic theories-why they're wrong, the harm they've done, and the theories that would vastly improve on them. Jeff Madrick-former New York Times business columnist and now Harper's economics columnist-mounts a comprehensive case against prevailing mainstream economic thinking, illustrating how it has damaged markets, infrastructure, and individual livelihoods, causing hundreds of billions of dollars of wasted investment; financial crisis after financial crisis; poor public education and public transportation; gross inequality of income and wealth, and stagnating wages; uncontrolled military spending; and a failed healthcare system that delivers far less than it costs. Using the Great Recession as his foremost case study, Madrick shows how the decisions America should have made before, during, and after the financial crisis were suppressed by popular theory, and how the consequences are still being felt here and around the globe. And he examines the too-often-marginalized good ideas of modern economics, and convincingly argues just how beneficial they might be if only they can gain greater traction among policy makers
Includes bibliographical references (pages 217-242) and index.
Keywords: Economics--United States